(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
This paper focuses on the performance analysis features of the patch antenna. This antenna is designed by using Flame Retardant 4 (FR4), and Roger 4350 substrate materials that will be operating in Wireless Local Area Network (WLAN). The frequency chosen for this paper is 2.4GHz and it has been chosen from IEEE 802.11 network uses for a Wireless Fidelity (WiFi) network. The proposed antenna was developed using Computer Simulation Technology (CST-MW) software. The proposed FR4 substrate shows a higher antenna bandwidth as compared to a Roger substrate, however the antenna gain and directivity was enhanced with Roger substrate. By using this substrate, the antenna gain was enhanced by 40%.